Long-term effect of masked hypertension management on cognitive functions in geriatric age: geriatric MASked hypertension and cognition follow-up study (G-MASH-cog MONITOR). Issue 4 (15th March 2021) - Balci, Cafer; Eşme, Mert; Sümer, Fatih; Asil, Serkan; Yavuz, Bünyamin; Tuna, Rana; Özsürekci, Cemile; Çalişkan, Hatice; Ünsal, Pelin; Şengül Ayçiçek, Gözde; Halil, Meltem; Cankurtaran, Mustafa; et al.
Abstract : Objectives: Masked hypertension, defined as nonelevated clinic blood pressure with elevated out of clinic blood pressure, has been associated with increased cardiovascular events, mortality and cognitive impairment. No evidence exists regarding the effect of treating masked hypertension. In this study, we followed-up the patients in the G-MASH-cog study for 1 year and aimed to examine the effect of the management of masked hypertension on cognitive functions. Methods: The G-MASH-cog study participants were followed-up for 1 year. In masked hypertensive individuals, lifestyle modification and antihypertensive treatment (perindopril or amlodipine) were initiated for blood pressure control. Measurements of cognitive tests and ambulatory blood pressure monitoring at baseline and at 1-year follow-up were compared. Results: A total of 61 patients (30 in masked hypertension group; 31 in normotensive group) were included. Mean age was 72.3 ± 5.1 and 59% of the participants were female. Compared with baseline ambulatory blood pressure measurement results, patients with masked hypertension had significantly lower ambulatory blood pressure measurement results after 1-year follow-up. The quick mild cognitive impairment test (Q-MCI-TR) score increased with antihypertensive treatment (Q-MCI score at baseline = 41(19–66.5), at 1 year = 45.5 (22–70), P = 0.005) in masked hypertensive patients. In the final model of the mixed-effects analysis, when adjusted for covariates, interaction effect of the masked hypertension treatment with time was only significant in influencing the changes in Q-MCI scores over time in patients aged between 65 and 74 years ( P = 0.002). Conclusions: Treatment of masked hypertension in older adults was associated with improvement in cognitive functions.